STRATEGI PENGELOLAAN OBJEK WISATA RELIGI GANTARANG LALANG BATA BERBASIS PARTISIPASI SOSIAL UNTUK KEMANDIRIAN DESA - Ainun Zahariyah Taufik; Ibrahim; Rusdi (STKIP Subang, 2026)
ABSTRACT This study aims to determine: 1) How factors influence community participation in the management of the Gantarang Lalang Bata religious tourist attraction. 2) To determine the management strategies of the Gantarang Lalang Bata religious tourist attraction in increasing community participation for village independence. The type of research used is descriptive qualitative. The data collection techniques used in this study are observation, interviews, and documentation. Data analysis was conducted in three stages, namely data reduction, data presentation, and conclusion drawing, accompanied by SWOT analysis. The results of this study are as follows: 1) The factors that influence community participation in the management of the Gantarang Lalang Bata religious tourist attraction include age, livelihood, and leadership (community and government figures). 2) The management strategy for the Gantarang Lalang Bata religious tourist attraction based on the results of the SWOT analysis is as follows: SO Strategy: Optimizing the role of the community as local guides and creative economic actors; WO Strategy: Forming a tourism awareness group (Pokdarwis) as the main manager and utilizing the potential for mutual cooperation to improve basic facilities on a regular basis; ST Strategy: Preserving local religious and cultural values so that they are not eroded by modernization and holding regular events (religious festivals) to maintain the existence and interest of tourists, and WT Strategy: Digitizing history and documentation.